Gender Representation in Narrative Texts in English Textbook: Questioning the Values through the 2013 Curriculum - Nurhidayah, Sri; Prihantini, Apsari Fajar; Efendi, Tri Achmad (Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to reveal gender values ​​in the narrative text of English textbook and how the values meet the requirement of the 2013 Curriculum. This research uses a qualitative approach. The data source is narrative text in English textbook published by the Ministry of Education and Culture. Data collected through documentation techniques by citing. Meanwhile, the data analysis procedure includes finding how many narrative texts are in the English textbook, reading the text carefully, taking notes and collecting citations. In addition, it is found that the narrative text was dominated by the values ​​of gender inequality. Gender inequality is still considered as a silent missile in today’s education and is still present in many stories or classic narrative texts in English textbooks. The researcher also found the unsuitability of the values​​with the 2013 Curriculum. Finally, based on the findings of this study, the researcher suggested that educational institutions pay more attention to the content of textbooks, not only in accordance with the current curriculum, but also according to student’s needs.